Role and Association of Inflammatory and Apoptotic Caspases in Renal Tubulointerstitial Fibrosis - You Ke; Hui Tang; Chen Ye; Chun-Tao Lei; Yu-Mei Wang; Hua Su; Chun Zhang; Hua-Jun Jiang (Karger Publishers, 2016)
Background/Aims: Caspases, an evolutionary conserved family of aspartate-specific cystein proteases, play pivotal roles in apoptotic and inflammatory signaling. Thus far, 14 mammalian caspases are identified and categorized into 3 distinct sub-types: inflammatory caspases, apoptotic initiator and apoptotic executioner. Caspase-1 is an inflammatory caspase, while caspase-7 belongs to apoptotic executioner. The roles and association of these two distinct types of caspases in renal tubulointerstitial fibrosis (TIF) have not been well recognized. Methods: Caspase-1 inhibitor Z-YVAD-FMK and caspase-7 siRNA were used in tubular epithelial cell line NRK-52E (TECs) to test their effects on transforming growth factor-beta1 (TGF-β1) stimulation. In vivo, Unilateral ureteral obstruction (UUO) animal model was employed in wild-type (WT) and caspase-1 knock out (KO) (caspase-1-/-) mice. Results: In current study, we found that caspase-7 was obviously activated in cultured TECs stimulated by TGF-β1 and in UUO model of WT mice. While in UUO model of caspase-1 KO mice, the increased caspase-7 activation was suppressed significantly along with reduced trans-differentiation and minimized extracellular matrix (ECM) accumulation, as demonstrated by western blot, Masson trichrome staining and immunohistochemistry. In addition, pharmacological inhibition of caspase-1 dampened caspase-7 activation and TECs' transdifferentiation induced by TGF-β1 exposure, which was consistent with in vivo study. Notably, caspase-7 gene knock down by specific siRNA abrogated TGF-β1 driven TECs' trans-differentiation and reduced ECM accumulation. Conclusions: Our study associated inflammatory and apoptotic caspases in TIF for the first time and we further confirmed that caspase-1 activation is an upstream event of apoptotic caspase-7 induction in TIF triggered by UUO and in TECs mediated by TGF-β1 induced transdifferentiation.